"A golden opportunity": Exploring interprofessional learning and practice in rural clinical settings. Issue 4 (July 2015) - Spencer, Judy; Woodroffe, Jessica; Cross, Merylin; Allen, Penny
Abstract Little is known about interprofessional practice (IPP) and interprofessional learning (IPL) in rural health services, despite national funding and continuing emphasis on increasing students' clinical placements in rural areas. This short paper outlines a study in Tasmania, Australia, which investigated how and under what contexts and conditions IPP and IPL occur in rural clinical settings, and the enabling factors and strategies that promote this learning and practice. This study employed a mixed method design comprising focus group discussions and a survey involving health professionals from two rural health services. The findings demonstrate that formal and informal arrangements, the collaborative nature of small, close-knit healthcare teams and patient-centred models of care employed in rural practice settings, provide ideal contexts for IPP and IPL. The study has implications for promoting organisational readiness for IPP and IPL and harnessing the potential of rural services to promote and develop students' interprofessional capability.